Comparative morphology of immature stages of two sympatric Tenebrionidae species, with comments on their biology - Wagner, Grzegorz K.; Gosik, Rafał (Zootaxa, 2016)
The mature larva and pupa of Neomida haemorrhoidalis are described and illustrated for the first time. The mature larva of Bolitophagus reticulatus is completely redescribed and illustrated, and its pupa is described for the first time. The differential diagnosis of the two species is presented. Information about their biology and life history is also given.